find the remainder when the polynomial p( x) =x ^61 + 61 is divided by x-1 ...please answer fast
Answers
Answered by
5
hello here is your answer by Sujeet yaduvanshi,
Given that,
polynomial. x^61+61
Now,
F(x)=x-1
f(x)=x-1=0
x=1
then,
putting the value of x in required polynomial,
x^61+61
(1)^61+61
1+61
62
Hence,
Required Remainder 62
that's all
Given that,
polynomial. x^61+61
Now,
F(x)=x-1
f(x)=x-1=0
x=1
then,
putting the value of x in required polynomial,
x^61+61
(1)^61+61
1+61
62
Hence,
Required Remainder 62
that's all
Answered by
4
Let see your answer !!!!!
![let \: p(x) = x ^{61} + 61 \\ \\ f(x) = x - 1 \\ \\ = > 0 = x - 1 \\ \\ = > - x = - 1 \\ \\ = > x = 1 let \: p(x) = x ^{61} + 61 \\ \\ f(x) = x - 1 \\ \\ = > 0 = x - 1 \\ \\ = > - x = - 1 \\ \\ = > x = 1](https://tex.z-dn.net/?f=let+%5C%3A+p%28x%29+%3D+x+%5E%7B61%7D++%2B+61+%5C%5C++%5C%5C+f%28x%29+%3D+x++-+1+%5C%5C++%5C%5C++%3D++%26gt%3B+0+%3D+x+-+1+%5C%5C++%5C%5C++%3D++%26gt%3B++-+x+%3D++-+1+%5C%5C++%5C%5C++%3D++%26gt%3B+x+%3D+1)
By remainder theorem
![p(1) = 1 ^{61} + 61 \\ \\ = 1 + 61 \\ \\ = 62 p(1) = 1 ^{61} + 61 \\ \\ = 1 + 61 \\ \\ = 62](https://tex.z-dn.net/?f=p%281%29+%3D+1+%5E%7B61%7D++%2B+61+%5C%5C++%5C%5C++%3D+1+%2B+61+%5C%5C++%5C%5C++%3D+62)
Hence , the remainder is 62.
Thanks :)))))
By remainder theorem
Hence , the remainder is 62.
Thanks :)))))
Similar questions